If x+y+z=0, show that x cube+y cube+z cube =3xyz
Answers
Answered by
3
first
x+y+z=0
x+y= -z--->(1)
so cubing on both sides on 1st equation
=>(x+y)cube= -(z)cube
(by using identity (a+b)cube=a cube + b cube +
3ab(a+b)
now substitute in that form you Wil get answer
substitute in x+y place take minus z
x+y+z=0
x+y= -z--->(1)
so cubing on both sides on 1st equation
=>(x+y)cube= -(z)cube
(by using identity (a+b)cube=a cube + b cube +
3ab(a+b)
now substitute in that form you Wil get answer
substitute in x+y place take minus z
Similar questions
Math,
9 months ago
Science,
9 months ago
Math,
9 months ago
CBSE BOARD XII,
1 year ago
English,
1 year ago
Music,
1 year ago
Social Sciences,
1 year ago
Social Sciences,
1 year ago